Optimising a handcrafted dialogue system design - Laroche, Romain; Putois, Ghislain; Bretier, Philippe (Proceedings of the 11th Annual Conference of the International Speech Communication Association (Interspeech), 2010)
In the Spoken Dialogue System literature, all studies consider the dialogue move as the unquestionable unit for reinforcement learning. Rather than learning at the dialogue move level, we apply the learning at the design level for three reasons: 1/ to alleviate the high-skill prerequisite for developers, 2/ to reduce the learning complexity by taking into account just the relevant subset of the context and 3/ to have interpretable learning results that carry a reusable usage feedback. Unfortunately, tackling the problem at the design level breaks the Markovian assumptions that are required in most Reinforcement Learning techniques. Consequently, we decided to use a recent non-Markovian algorithm called Compliance Based Reinforcement Learning. This paper presents the first experimentation on online optimisation in dialogue systems. It reveals a fast and significant improvement of the system performance with by average one system misunderstanding less per dialogue.